Greener manufacturing and operations : from design to delivery and back - Sarkis, Joseph (Greenleaf, 2001)
This timely work examines one core corporate function that has a profound and direct impact on corporate environmental performance - manufacturing and operations. It captures state-of-the-art and future practices in environmental manufacturing and operations practices and issues in one volume.